(untitled) (Research, Society and Development, 2020)
The Bung Tomo Training Ship with a weight of 12 S7 GT, a LWT of 899 tons and a LOA of 63 m, is the only training ship owned by Surabaya Merchant Marine Polytechnic. This ship was made in 2 017 with a capacity of 300 people. The existence of the ship is very important for the learning process at Surabaya Merchant Marine Polytechnic because it is used by cadets to sail practice every Saturday and Sunday. Damage to the ship’s machinery can be caused by poor planning and implementation and is known after the ship has begun to operate. To prevent greater damage or disturbance to the Bung Tomo Training Ship, an analysis of the failure of the machinery maintenance system is needed. This research aims to obtain analysis of the failure of machinery on the Bung Tomo Training Ship by using the Failure Mode and Effects Analysis (FMEA) through identification of the causes of failure, the impact caused and possible remedial measures to prevent greater damage. Several components with high RPN are deserve to be a concern or top priority in machinery maintenance of the Bung Tom o Training Ship, namely: sea water pump, freshwater pump, pipeline, OWS, freshwater cooling, sea water cooling pump, and fresh water generator.